STOCK PORTFOLIO PERFORMANCE BASED ON STOCK VOLATILITY: A STUDY OF INDONESIA STOCK MARKET - Kusno, John Iwan; Teja, Adrian (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
The aim of the study was to investigate the relevancy of capital asset pricing model (CAPM) in Indonesia. CAPM states investor who has willingness to take higher risk should compensate with higher return as compensation. Hypothesis testing uses the one sample t-test to validate the return portfolio is not equal to zero. The result of the study revealed that portfolio with highest risk did not provide highest return. Supposition of the results is because limitation of CAPM theory (frictionless market and everyone has risk averse profile). This creates low risk anomaly phenomenon in Indonesia stock market which lower risk portfolio can provide higher return and contractive monetary policy magnify the portfolio performance differences.